Reduction of sphingomyelinase activity associated with progranulin deficiency and frontotemporal dementia - Nicholas R. Boyle; Stephanie N. Fox; Aniketh S. Tadepalli; Nicholas T. Seyfried; Thomas Kukar; Eliana M. Ramos; Alissa L. Nana; Salvatore Spina; Lea T. Grinberg; Bruce L. Miller; William W. Seeley; Andrew E. Arrant; et al. (Neurobiology of Disease)
Loss-of-function mutations affecting the lysosomal protein progranulin are a leading cause of frontotemporal dementia. Progranulin mutations cause abnormalities in lysosomal lipid processing, particularly of sphingolipids, major components of neural cell membranes that play important signaling roles in the brain. Most work in this area has focused on two classes of sphingolipids, gangliosides and cerebrosides. Here, we examined enzymes involved in metabolism of another class of sphingolipids, the sphingomyelins, in both mouse models and patients with progranulin insufficiency. Acidic sphingomyelinase activity was decreased in progranulin knockout, but not heterozygous, mice. This resulted from post-transcriptional loss of acid sphingomyelinase (Smpd1) protein. Progranulin interacted with acid sphingomyelinase in immunoprecipitation and proximity ligation assays, suggesting a co-trafficking role like progranulin plays with other lysosomal enzymes. Consistent with that hypothesis, restoring progranulin in knockout mice using AAV-progranulin gene therapy corrected acid sphingomyelinase deficits. In post-mortem brain tissue from patients with frontotemporal dementia due to heterozygous progranulin mutations, neutral, but not acidic, sphingomyelinase activity was decreased. Neutral sphingomyelinase 2 (SMPD3), the predominant neutral sphingomyelinase in the brain, was reduced in patients with progranulin mutations. A similar trend (p = 0.0586) was seen in patients with sporadic frontotemporal lobar degeneration with type A TDP-43 pathology, but not in other types of frontotemporal lobar degeneration. The reduction of neutral sphingomyelinase 2 occurred in frontal, but not occipital cortex, correlating with the selective vulnerability of frontal regions seen in FTD. These data shed light on the role of progranulin in sphingomyelin metabolism and of this pathway in frontotemporal dementia.